Mouthwash Containing Vitamin E, Triamcinolon, and Hyaluronic Acid Compared to Triamcinolone Mouthwash Alone in Patients With Radiotherapy-Induced Oral Mucositis: Randomized Clinical Trial - Agha-Hosseini, Farzaneh; Pourpasha, Mona; Amanlou, Massoud; Moosavi, Mahdieh-Sadat (Frontiers in Oncology, 2021)
One of the most common side effects of radiotherapy in head and neck cancers is mucositis. Despite all the studies conducted on new therapies for oral mucositis caused by radiation therapy, a single standard treatment strategy has not yet been developed. In the present study, for the first time, the effectiveness of treatment with a combined mouthwash containing vitamin E (as an antioxidant), triamcinolone (as an anti-inflammatory agent) and hyaluronic acid (HA) (as a local reducer used for reducing the effects of ROS on the mucosa, with ameliorative effects (improving the healing process)) compared to triamcinolone mouthwash alone was investigated in patients with radiotherapy-induced oral mucositis. This study was a randomized triple-blind clinical trial performed on 60 patients undergoing radiotherapy on an outpatient basis. The combined mouthwash containing vitamin E, triamcinolone, and hyaluronic acid compared to triamcinolone mouthwash alone was prescribed for 4 weeks. The severity of oral mucositis was assessed based on the WHO classification and the intensity of pain was assessed using the numerical pain intensity scale. According to the analysis performed in the first, second, third and fourth weeks, the reduction of oral mucositis grade in the intervention group was significantly higher than in the comparison group. In the first, second, third, and fourth weeks, the reduction in pain intensity in the intervention group was significantly higher than in the comparison group (P < 0.001). The combined mouthwash containing vitamin E, hyaluronic acid and triamcinolone acetonide can be used as an effective treatment for oral mucositis caused by radiation therapy, which is probably the result of antioxidant, anti-inflammatory and improved healing process mechanisms due to the biological nature of the components of this mouthwash. Trial registration: This study was registered in the WHO Primary registry (IRCT) with the code IRCT20190428043407N. Registered 20 July 2019, https://www.irct.ir/trial/39231.